The Implementation of Peer Tutoring Strategy in Teaching Writing at the Tenth Grade of SMAN 1 Lemahabang - Septianis, Melaty (Universitas Swadaya Gunung Jati, 2017)
Peer tutoring strategy is learning strategy where some students teach or help another student in learning process. The aim of this research were to know if peer tutoring strategy effective in teaching writing at the tenth grade of SMAN 1 Lemahabang and if there any positive responses from the students through the implementation of peer tutoting strategy in teaching writing. This research was quantitative research which used pre-expreimental research and the research design of this study was The One-Group Pre-Test and Post-Test Design. The researcher used two instruments of data collections The first instrument was test which covered pre-test and post-test. The second instrument was questionnaire. The population of this research was tenth grade of SMAN 1 Lemahabang, and X MIPA 1 as a sample of this reseach. This research focussed on recount text as the learning material of writing. After got the data of test, the writer used formula from McMillan (2001:620) to analysed its. The test result showed that there a significant result between taccount and ttable. Those were the score of taccount was 18,01 meanwhile ttable was 2,024. It can be concluded that the implementation of peer tutoring strategy was effective in teaching writing at the tenth grade of SMAN 1 Lemahabang. Through the questionnaire, the writer also knew that there were any postive responses from the students toward the implementation of peer tutoring strategy in teaching writing. Such as the most of students strongly agree and agree that strategy can help them to be easy in writing recount text learning.Keywords : Writing, Peer Tutoring Strategy, Recount Text